The end of American exceptionalism: an enlightened corrections - Cullen, Francis T. (Criminology & public policy, 2022)
Research Summary The United States is at a turning point in the history of corrections. Suddenly and surprisingly, the era of mass incarceration ended around 2010. Since that time, prison populations, public punitiveness, and get-tough rhetoric have declined. A challenging question remains, however: Now what? Doing more of the same is foolish but likely. Prison reform is inhibited by the twin realities that states have limited budgets and have existing prisons that are rarely shuttered. New thinking is needed to move beyond these restrictions. One guide for a cognitive shift is Steven Pinker's Enlightenment Now in which he argues that sustained improvement in human well-being in the United States and across the globe is due to the Enlightenment principles of reason, science, humanism, and progress. In this context, an "enlightened corrections" is possible in which policies and practices are evaluated by the four ideals articulated by Pinker. As one example, mass imprisonment is shown to be irrational, unscientific, inhumane, and bereft of a future. By contrast, more promising policies seek to nourish offenders by offering redemption and by using community supervision to build quality relationships that provide a means for targeting risk factors for intervention. Policy Implications The key policy implication is the proposal to place prison reform within the Biden Administration's support for infrastructure improvement. Funded by the federal government, a "Build Back Better Prison Experiment" would be undertaken in which 10 experimental prisons—designed from a clean slate and selected through a competition—would be created and evaluated. The goal is to establish prisons that are rational in their planning, are evidence based, improve offenders’ lives, and foster a new era of progress in American corrections.